Depression in Rural Communities and Primary Care Clinics in Chiapas, Mexico - Elliott, Michael L. (J Epidemiol Glob Health, 2019)
Depression is a leading cause of disability worldwide and can be diagnosed and treated in primary care clinics. No studies to date have demonstrated the prevalence of depression in rural, primary care settings in Mexico. The objective of this study is to describe the prevalence of visits for depression in primary care settings in one group of rural communities within Chiapas, Mexico. We performed a cross-sectional, retrospective study of depression prevalence in primary care clinics in the Sierra region of Chiapas, Mexico during the calendar year of 2014. We determined the average depression prevalence is 7.9% (6 community clinics, n = 4555). The prevalence of depression in rural Chiapas, Mexico is much higher than the Mexican national average of 4.0–4.5% found in a home-based survey. Further efforts to understand the causes, develop improved mental health services in primary care, and reduce the higher burden of depression in rural communities in Mexico are urgently needed.